Some Implications for Using a Diagnostic Test in English Language Course at Post-Secondary Level - Bakić-Mirić, Nataša M.; Lončar-Vujnović, Mirjana N. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
This paper addresses a relatively new type of testing in English language called diagnostic test(ing). This type of test is used to accelerate students’ performance during the English language course at post-secondary level. The purpose of this test is to help teachers determine students’ English language skills and to give an outlook into areas where students exhibit weaknesses and need to work on to improve during the course.